Potensi Daya Tarik Wisata Grhatama Pustaka Yogyakarta Sebagai Wahana Rekreasi - Eko Sugiarto; Sabda Elisa Priyanto (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This research is a descriptive study, looking for the potential attractions of Grhatama Pustaka Yogyakarta as a recreation place based on the perspective of visitors. Primary data were collected by interview and observation methods. This primary data is then supplemented with secondary data obtained from a variety of relevant literature. The results of this study are the potential of the tourist attraction of Grhatama Pustaka Yogyakarta as a place of recreation based on the perspective of the visitors in uniqueness, which cannot be found anywhere else. The conclusion of this research is Grhatama Pustaka Yogyakarta is interesting to visit because it is unique so it has the potential to become a tourist attraction. However, at this time the function of Grhatama Pustaka Yogyakarta is still not yet optimal as a recreation place. Therefore, further studies are still needed on developing the tourism potential of Grhatama Pustaka Yogyakarta so that its function as a recreation place can be better.